2005
DOI: 10.1108/13673270510610341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management effectiveness factors: the role of HRM

Abstract: PurposeWithin the search of the key factors that explain knowledge management (KM) effectiveness, this paper aims to advance a simultaneously conceptual and practical framework that links human resource management (HRM) and KM.Design/methodology/approachA literature‐based preliminary framework assumes that a number of critical KM characteristics and KM‐related human resource (HR) practices impact on KM effectiveness. Qualitative methods are used for data collection and analysis. Three knowledge‐intensive Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 76 publications
3
87
0
3
Order By: Relevance
“…This can be supported by Oltra's (2005) results who asserted on the fact that unless HRM and KM have been both taken seriously by management, there is little need to talk about the role of HRM practices in KM. This was discussed by Hislop (2003) who looked at it from employees' point of view and concluded that the type of HRM policies and practices adopted in an organization has been found to affect people's willingness to share knowledge.…”
Section: Hrm Practices and Km Processessupporting
confidence: 49%
See 1 more Smart Citation
“…This can be supported by Oltra's (2005) results who asserted on the fact that unless HRM and KM have been both taken seriously by management, there is little need to talk about the role of HRM practices in KM. This was discussed by Hislop (2003) who looked at it from employees' point of view and concluded that the type of HRM policies and practices adopted in an organization has been found to affect people's willingness to share knowledge.…”
Section: Hrm Practices and Km Processessupporting
confidence: 49%
“…Many studies discussed the relationship between human resource management and knowledge management process (see for example Hislop, 2003;Oltra, 2005;Chiang et al, 2011;Fong et al, 2011;Jimenez-Jimenez & Sanz-Valle, 2013). Other studies discussed the relationship between human resource management and organizational commitment (see for example Edgar & Geare, 2005;Sanders et al, 2008;Juhdi et al, 2011;Zaitouni et al, 2011;Imran & Ahmed, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the literature review related to this study, many researchers claimed that human resources practices play an important role in facilitating employees' absorption, transfer, sharing and creation of knowledge [25]. Previously, many researchers neglect to conduct research on the human capital issue [26]. The literature of knowledge transfer has made only partial and limited use of HRM concepts and frameworks [27].…”
Section: B Strategic Human Resource Management Andmentioning
confidence: 97%
“…According to [36], it adds to this discussion by finalizing that human beings are the critical knowledge creators and bearers. Great care has to be taken to increase human capability and organizational performance.…”
Section: B Strategic Human Resource Management Andmentioning
confidence: 99%
“…An organisation's reward and recognition system demonstrates the level of value that an organisation places on individuals (Edvardsson, 2008). In leading KM endeavours, HRM functions should be implemented in such a way that they promote trust across an organisation (Oltra, 2005;Truss, Mankin, & Kelliher, 2012) as well as willingness and opportunity to share knowledge (Sitlington, 2012). An organisational environment that is established on trust and desirable HRM functions, allows individuals to take an active role in the KM practices.…”
Section: Role Of Hrm In Kmmentioning
confidence: 99%